THE USE OF ICT IN ENGLISH LEARNING PROJECT : PERCEPTION OF PUBLIC HEALTH SCIENCE STUDY PROGRAM STUDENTS OF STIK BINA HUSADA PALEMBANG ACADEMIC YEAR 2024/2025 - PAMUJI, ARIEF; WAHYUDI, AGUS; MARTUTI, RIRIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
ICT not only allows access to wider educational resources, but also enriches the learning experience through various digital applications and platforms. In the context of project-based learning, digital technology plays a very important role in supporting collaborative processes, facilitating communication, and providing opportunities for students to develop their English skills creatively and interactively. However, there are challenges faced in the utilization of ICT among students, especially related to the limitations of technological infrastructure and digital literacy. Perception is the process by which individuals organize and interpret stimuli from their environment to form a picture of their world. This study uses Quantitative research. Quantitative research is a type of research conducted by collecting numerical data. Researchers will use a questionnaire as an instrument in collecting data. The scale used is Likert, a choice for the questioner to measure from strongly agree, agree, neutral, disagree, and strongly disagree. In this study, there were 39 students of the Public health study program at STIK Bina Husada Palembang in the 2024/2025 academic year who participated in this study, Students were asked to fill out the questionnaire adapted from Baran, E., & Maskan, A. (2021) the questionnaire filling period is November 11-12, 2024. The integration of ICT in English learning projects has been highly effective in enhancing the learning experiences of students in the Public Health Science Study Program at STIK Bina Husada Palembang. ICT tools and platforms have significantly contributed to improving discussions, project management, collaboration, and confidence in presentations, while also fostering communication and understanding through translation applications and social media. Despite the positive impact, challenges such as technical difficulties, limited internet access, and varying levels of ICT proficiency highlight areas for improvement. ABSTRAKTIK tidak hanya memungkinkan akses ke sumber daya pendidikan yang lebih luas, tetapi juga memperkaya pengalaman belajar melalui berbagai aplikasi dan platform digital. Dalam konteks pembelajaran berbasis proyek, teknologi digital memainkan peran yang sangat penting dalam mendukung proses kolaboratif, memfasilitasi komunikasi, dan memberikan kesempatan bagi siswa untuk mengembangkan keterampilan bahasa Inggris mereka secara kreatif dan interaktif. Namun, ada tantangan yang dihadapi dalam pemanfaatan TIK di kalangan siswa, terutama terkait dengan keterbatasan infrastruktur teknologi dan literasi digital. Persepsi adalah proses ketika individu mengatur dan menafsirkan rangsangan dari lingkungan mereka untuk membentuk gambaran tentang dunia mereka. Penelitian ini menggunakan penelitian Kuantitatif. Penelitian kuantitatif merupakan jenis penelitian yang dilakukan dengan mengumpulkan data numerik. Peneliti akan menggunakan kuesioner sebagai instrumen dalam mengumpulkan data. Skala yang digunakan adalah Likert, pilihan bagi penanya untuk mengukur dari sangat setuju, setuju, netral, tidak setuju, dan sangat tidak setuju. Dalam penelitian ini, terdapat 39 mahasiswa program studi Kesehatan Masyarakat STIK Bina Husada Palembang tahun ajaran 2024/2025 yang mengikuti penelitian ini, Mahasiswa diminta untuk mengisi kuesioner yang diadaptasi dari Baran, E., & Maskan, A. (2021) periode pengisian kuesioner adalah 11-12 November 2024. Integrasi TIK dalam proyek pembelajaran Bahasa Inggris sangat efektif dalam meningkatkan pengalaman belajar mahasiswa di Program Studi Ilmu Kesehatan Masyarakat STIK Bina Husada Palembang. Alat dan platform TIK telah berkontribusi secara signifikan untuk meningkatkan diskusi, manajemen proyek, kolaborasi, dan kepercayaan diri dalam presentasi, sementara juga mendorong komunikasi dan pemahaman melalui aplikasi penerjemahan dan media sosial. Meskipun berdampak positif, tantangan seperti kesulitan teknis, akses internet terbatas, dan berbagai tingkat kemahiran TIK menyoroti area yang perlu ditingkatkan.